A LINGUISTIC LANDSCAPE IN THE DIGITAL ERA: A CASE STUDY IN MEDAN - Dewi Nurmala; Diana Sopha Diana Sopha; Ayu Melati Ningsih; Vera Kristiana; Muhammad Kiki Wardana (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The study investigated the linguistic landscape of downtown looks like in the digital era and how the digital era influenced changes in the linguistic landscape in downtown Medan. This study uses qualitative methods. The data collected consists of written data and the types of media on signboards in the city of Medan. Data analysis was carried out in three steps, namely: 1) data condensation, which is the process of reading the collected data and determining the data, in this case data in the form of writing and types of signboard media, 2) data display, which is displaying selected data in the form of billboards in the central area of Medan, and 3) drawing conclusions, which is finding results after analyzing the data. After analysing data, it was found that 38% signage uses Indonesian, 30% uses English, 27% uses language mixing and the rest, 5% uses traditional language and other foreign languages. Conventional signage has given way to new, more dynamic, and interactive forms thanks to the digital age. These include LED boards, electronic screens, and the incorporation of digital components like social media and QR codes in signboards and advertisement. Digital media forms display more modern language choices, posing a threat to the national language and isolated regional languages in their own countries. The research highlights the linguistic landscape that has emerged in the digital era.